A Panel Data Analysis on FDI and Exports - Martin Falk; Mariya Hake (FIW - Research Centre International Economics, 2008)
The present paper investigates the link between exports and the outward FDI stock using a panel of industries and seven EU countries for the period 1973-2004. In particular, we use the panel causality tests developed by Holtz-Eakin, Newey, and Rosen (1988). Estimates using system GMM estimators show that exports cause FDI but not vice versa. The long-run elasticity of the outward FDI stock with respect to exports is 0.78 and highly significant. Separate estimates by destination country yields the same result that exports cause outward FDI but the effect is only significant for the CEE countries and other developed countries (i.e. United States, Japan, Canada, Switzerland, Norway, etc.).
Keywords: F10; F21; 330; exports; FDI; dynamic panel data methods